Phytophthora capsici Epidemic Dispersion on Commercial Pepper Fields in Aguascalientes, Mexico - Adrián Zapata-Vázquez; Mario Sánchez-Sánchez; Alicia del-Río-Robledo; Héctor Silos-Espino; Catarino Perales-Segovia; Silvia Flores-Benítez; Mario Martín González-Chavira; Luis Lorenzo Valera-Montero (The Scientific World Journal)
Chili pepper blight observed on pepper farms from north Aguascalientes was monitored for the presence of Phytophthora capsici during 2008–2010. Initially, ELISA tests were directed to plant samples from greenhouses and rustic nurseries, showing an 86% of positive samples. Later, samples of wilted plants from the farms during the first survey were tested with ELISA. The subsequent survey on soil samples included mycelia isolation and PCR amplification of a 560 bp fragment of ITS-specific DNA sequence of P. capsici. Data was analyzed according to four geographical areas defined by coordinates to ease the dispersal assessment. In general, one-third of the samples from surveyed fields contained P. capsici, inferring that this may be the pathogen responsible of the observed wilt. Nevertheless, only five sites from a total of 92 were consistently negative to P. capsici. The presence of this pathogen was detected through ELISA and confirmed through PCR. The other two-thirds of the negative samples may be attributable to Fusarium and Rhizoctonia, both isolated instead of Phytophthora in these areas. Due to these striking results, this information would be of interest for local plant protection committees and farmers to avoid further dispersal of pathogens to new lands.